The Hafsids and the Mamluks competed for the caliphate during the Mongol occupation (657-675 AH) - Assis.Lect. Haitham oudah kadhim (Journal of College of Education, 2023)
Praise be to God, Lord of the worlds, and prayers and peace be upon our Master and Prophet Muhammad, and his pure God... The relations between the East and the Maghrib have been linked since the early ages and formed a geographical extension between two Islamic regions that helped the process of permanent communication between them at the various political, economic and cultural levels. The East and the Maghrib were accompanied by decisive developments during a dangerous transitional period. The Abbasid caliphate no longer had complete control over the Islamic East, and the position of the caliphate became formally under the authority of the Mamluks in light of the escalation of external dangers that threatened both the Mamluk authorities in the Levant and the Hafsids in the Maghreb, especially after the dissolution and demise of the Abbasid caliphate from events and transformations on the internal and external levels, which had a profound impact on the nature of relations between the two parties at the time to raise a major problem centered on the extent of the impact of events and developments. On the course and drawing the curve of relationships Between the two Mamluk and Hafsid states during that period, and what are the positions of the Mamluks regarding the prevailing events in the Hafsid sultanate, and how did they deal with that, and what are the active parties and contributing to the consolidation, effectiveness and continuity of these relations between the two regions and the consolidation of the features of cultural unity between the two countries and the role that the Hafsid authority played in this period in front of their Mamluk counterparts in making effective and articulated events in light of the absence of the role of the Abbasid caliphate, and were the Mamluks and Hafsid able to Overcome this apathy and tension in relations in the face of the dangers that threaten the Islamic world.
Keywords: Hafsid Mamluks , Islamic Caliphate , Mongols